(untitled) (Annals of Medical Research, 2024)
Aim: The objective of this study is to illustrate the impact of disc prosthesis instrumentation in the intervertebral disc space following discectomy on cervical lordosis (CL) as observed in radiographic images by measuring the Cobb angle and cervical disc height taken before and after surgery. Furthermore, the study seeks to evaluate the functionality of the disc prosthesis employed. The objective was to evaluate the functionality of the surgical procedure and the type of disc prosthesis employed. Materials and Methods: A total of 106 patients with cervical disc herniation who underwent surgical intervention using cervical disc prostheses were included in the study. Pre- and post-surgical lateral direct radiographic evaluations were obtained from each patient. The following variables were recorded for evaluation: preoperative Cobb angles, cervical disc height, surgical level, age, and gender. Results: The most frequent site of cervical disc operation was the C5-6 level. There was a significant increase in the cervical Cobb angle after surgery, as well as a significant increase in postoperative disc height in comparison to preoperative values. The change in Cobb angle and disc height was found to be statistically significant (p < 0.05). Conclusion: A variety of cervical interbody grafts are currently in use. The use of cervical disc prostheses in cervical disc herniation surgery allows achieving optimum lordotic angulation. There is a continued need for new studies to support our physical examination findinds on the long-term clinical follow-up.